Four Decades of Intergenerational Educational Mobility in Sub-Saharan Africa. Issue 5 (4th May 2022) - Razzu, Giovanni; Wambile, Ayago
Abstract: Using nationally representative survey data from 34 countries, we assess the extent of intergenerational educational mobility for three-quarters of Africa's population, over four decades and by gender. We employ both transition probability matrices and regression-based estimates of intergenerational elasticities and correlation coefficients. We find that the educational status of parents is a strong determinant of their children's educational outcomes, but the strength of this link has diminished in Africa between 1960 and 1999, particularly since the 1980s. We also find that there are considerable differences between countries and by gender. Those in the Southern and Central African region and those with historical links to former British colonies experience relatively higher intergenerational mobility in education. Intergenerational educational mobility is less pronounced for daughters than for sons and mother's education is generally more strongly associated with children's educational attainment than fathers' education.